Neonatal Health of Parents and Cognitive Development of Children - Claus Thustrup Kreiner; Hans Henrik Sievertsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2018)
This paper documents a strong relationship between birth endowments of parents and the cognitive development of their children. The association between maternal birth weight and child school test scores corresponds to 80 percent of the association between the child's own birth weight and test scores (both in univariate and multivariate settings). We find a strong relationship, even when controlling for family differences, by looking at birth weight variation between sisters and the test score outcomes of their children, and when controlling for parental education and economic resources. Child test scores are also strongly related to paternal birth weight. To assess external validity, we replicate recent results from the US on the relationship between child birth weight and test scores. Our intergenerational results suggest that inequality in birth endowments may be important for inequality in key outcomes of the next generation.
Keywords: I12; J13; J24; 330; Neonatal health; human capital formation; intergenerational dependency